Collateral Clock Is More Important Than Time Clock for Tissue Fate: A Natural History Study of Acute Ischemic Strokes. Issue 9 (September 2018) - Vagal, Achala; Aviv, Richard; Sucharew, Heidi; Reddy, Mahati; Hou, Qinghua; Michel, Patrik; Jovin, Tudor; Tomsick, Thomas; Wintermark, Max; Khatri, Pooja
Abstract : Background and Purpose—: Although perfusion abnormality is an increasingly important therapeutic target, the natural history of tissue at risk without reperfusion treatment is understudied. Our objective was to determine how time affects penumbral salvage and infarct growth in untreated acute ischemic stroke patients and whether collateral status affects this relationship. Methods—: We used a prospectively collected, multicenter acute stroke registry to assess acute stroke patients who were not treated with intravenous thrombolysis or endovascular treatment. We analyzed baseline computed tomography angiogram and computed tomography perfusion within 24 hours of stroke onset along with follow-up imaging and assessed time from stroke onset to baseline imaging, ASPECTS (Alberta Stroke Program Early CT Score), vessel occlusion, collaterals, ischemic core, and penumbra. Penumbral salvage and infarct growth were calculated. Correlations between time and penumbral salvage and infarct growth were evaluated with Spearman correlation. Penumbral salvage and infarct growth were compared between subjects with good versus poor collateral status using the Wilcoxon rank-sum test. Clinical and imaging factors affecting penumbral salvage and infarct growth were evaluated by linear regression. Results—: Among 94 untreated stroke patients eligible for this analysis, the mean age was 65 years, median National Institutes of Health Stroke Scale score was 13, and median (range) time from stroke onset to baseline imaging was 2.9 (0.4–23) hours. There was no correlation between time and salvaged penumbra ( r =0.06; P =0.56) or infarct growth ( r =−0.05; P =0.61). Infarct growth was higher among those with poor collaterals versus those with good collaterals (median, 52.3 versus 0.9 cm 3 ; P <0.01). Penumbral salvage was lower among those with poor collaterals compared with those with good collaterals (poor, 0 [0–0]; good, 5.9 cm 3 [0–29.4]; P <0.01). Multivariable linear regression demonstrated that collaterals, but not time, were significantly associated with infarct growth and penumbral salvage. Conclusions—: In this natural history study, penumbral salvage and infarct growth were less time dependent and more a measure of collateral flow. Abstract : Supplemental Digital Content is available in the text.